TINJAUAN YURIDIS PENERAPAN LARANGAN PERSEKONGKOLAN TENDER MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT (STUDI KASUS DI KANTOR LAYANAN PENGADAAN SECARA ELEKTRONIK PROVINSI RIAU) - Hutahaean, Irvan Juanda; Firdaus, Firdaus; Ismi, Hayatul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The procurement of goods or services in a project of a company or governmentagency is often through tenders. This is intended by the tender organizer to get the price ofgoods or services that are in accordance with the standards and with the best possiblequality. In essence, the implementation of tenders must meet the principles of fairness,openness, and non-discrimination. In addition, tenders must pay attention to things that donot contradict the principle of unfair business competition.The type of research in this type of research is sociological law research, namely insociological law research, law is conceptualized on social institutions that are actuallyrelated to other social variables. This research is descriptive, i.e. to give as precise a word aspossible about people, circumstances or other symptoms.The conclusion of this study is, first, unfair business competition is competitionbetween business actors in carrying out production and/or marketing activities of goodsand/or services that are carried out in a dishonest or unlawful way or hindering businesscompetition. Second, tender conspiracy is an activity that is usually carried out by businessactors by making agreements to win tenders These activities often result in obstacles forbusiness actors who are not involved in the agreement and further impacts can result inlosses for the organizers because there are irregularities regarding prices. Third, in theimplementation of tender bidding in Riau province, the main goal that LPSE Riau Provincewants to achieve is to provide balanced opportunities for all bidders